2018
DOI: 10.1097/ccm.0000000000003030
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Level Versus Lactate Clearance for Predicting Mortality in Patients With Septic Shock Defined by Sepsis-3

Abstract: Our findings indicate lactate and lactate clearance are both useful targets in patients with septic shock defined by Sepsis-3. Serum lactate level at 6-hour can be an easier and more effective tool for prognosis of septic shock patients who were treated with protocol-driven resuscitation bundle therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
152
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(169 citation statements)
references
References 23 publications
13
152
1
3
Order By: Relevance
“…Nguyen et al [7] showed that a lower ΔLac 0-6h, obtained at 0h and 6h after admission to ED, was significantly associated with in-hospital mortality in 111 adult patients with severe sepsis or septic shock. Similarly, Ryoo et al [8] reported that median 6h repeated lactate concentrations and ΔLac 0-6h were significantly associated with 28-day mortality in 1,060 adult patients with septic shock. In contrast, the raw data for ΔLac varied considerably, resulting in a lower diagnostic ability [7,8].…”
Section: Dynamic Lactate Indexmentioning
confidence: 87%
See 3 more Smart Citations
“…Nguyen et al [7] showed that a lower ΔLac 0-6h, obtained at 0h and 6h after admission to ED, was significantly associated with in-hospital mortality in 111 adult patients with severe sepsis or septic shock. Similarly, Ryoo et al [8] reported that median 6h repeated lactate concentrations and ΔLac 0-6h were significantly associated with 28-day mortality in 1,060 adult patients with septic shock. In contrast, the raw data for ΔLac varied considerably, resulting in a lower diagnostic ability [7,8].…”
Section: Dynamic Lactate Indexmentioning
confidence: 87%
“…Similarly, Ryoo et al [8] reported that median 6h repeated lactate concentrations and ΔLac 0-6h were significantly associated with 28-day mortality in 1,060 adult patients with septic shock. In contrast, the raw data for ΔLac varied considerably, resulting in a lower diagnostic ability [7,8]. However, in the systematic review and meta-analysis for ΔLac, Zang and Xui [11] concluded that the diagnostic performance of ΔLac remained at a moderate accuracy level in the heterogenous ICU population.…”
Section: Dynamic Lactate Indexmentioning
confidence: 87%
See 2 more Smart Citations
“…In brief, aggressive uids infusion and vasopressors were applied with blood pressure monitoring. Lactate levels were checked via venous or arterial blood gas analysis, and a central venous catheter was placed routinely for administering high dose vasopressors and repetitive sampling [10,11].…”
Section: Data Collection and De Nition Of Variablesmentioning
confidence: 99%